Association between platelet indices and risk of preeclampsia in pregnant women. (3rd October 2022) - Wu, Jinjuan; Zhang, Jing; Yang, Jinying; Zheng, Thomas Qintian; Chen, Yu-Ming
Abstract: We aimed to examine the association between the platelet indices and the risk of preeclampsia (PE) at different gestational weeks (GW) to explore the feasibility of early prediction of PE with these indices. About 7314 normotensive pregnant women and 396 PE patients were included and platelet indices, including platelet count (PC), plateletcrit (PCT), platelet distribution width (PDW), mean platelet volume (MPV) at different gestational weeks (1–12, 13–28, 29–32, 33–36 and 37–41 GW) were compared in two statistical methods. Patients with PE tended to have higher means of PC, PCT, PDW and MPV than normal pregnant women at early stage of pregnancy. The odds of PE were significantly increased with the increase of PC, PCT, PDW and MPV both at 13–28 GW and 29–32 GW, which indicated that increased values of PC, PCT, PDW and MPV at 13-32 GW were associated with greater subsequent risk of preeclampsia. Increased PC, PCT, PDW and MPV may have potential to predict preeclampsia before the disease onset. Impact Statement: What is already known on this subject? Previous studies indicated that preeclampsia patients may have decreased platelet count (PC), plateletcrit (PCT) and increased platelet distribution width (PDW) and mean platelet volume (MPV). Increased PDW and MPV or decreased PC/MPV may have predictive values for PE. What do the results of this study add? The discrepancy with previous studies lay in the increased values of PC and PCT in PE patients at early stage of pregnancy. The study indicated that increased PC, PCT, PDW and MPV may have potential to predict preeclampsia far ahead of the disease onset. The results may reflect the abnormal turnover of platelets in PE patients. What are the implications of these findings for clinical practice and/or further research? These findings may help to guide early interventions before progress to overt preeclampsia by predicting onset of preeclampsia via easily available platelet indices in early weeks of gestation, which is especially valuable in areas lacking medical resources. The inconsistency with previous studies can facilitate researchers to further explore the coagulation mechanism beneath preeclampsia and pay more attention to the dynamic changes of platelet indices and other coagulation indices during pregnancy.